Spatial Segregation of Diploid and Polyploids Spined Loaches (Сobitis elongatoides–taenia–tanaitica) in the River Systems of Western and Central Ukraine - Mezhzherin , S. V.; Tsyba, A. O.; Rostovska , O. V. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2024)
The investigation examines the structure of diploid and polyploid populations within the spined loach group (Сobitis elongatoides–taenia–tanaitica) in the water systems of Western and Central Ukraine, including the Danube River, Dniester River, Southern Bug River, Vistula River, Middle and Upper Dnipro River basins. The study reveals a bipolarity in settlement structure, with a sharp prevalence of either diploids or polyploids, and no discernible geographical trends in spatial distribution. Clonal hybrid polyploids, which make up 70 % of the individuals studied in the region, are most common in settlements along the main river channels, as well as in the middle and lower reaches of first and second-order tributaries. Populations where diploid specimens of the parent species are predominant are located in accessory systems, tributaries of the third and higher orders, upper reaches of first and second-order tributaries, and lakes. This spatial segregation arises from historical circumstances rather than ecological preferences, primarily due to the distance from water corridors through which polyploids invaded in the 1960s‒1970s. The displacement of diploid individuals by clonal hybrid polyploids is a universal phenomenon. This is due to the advantages of parthenogenetic reproduction and higher survival rates of polyploids in modern environmental situations.